DFAM Based Multi-Material 3D Printing Using Conductive and Flexible Filaments - Rautio, Timo; Kumpula, Jani; Mäntyjärvi, Kari; Mäkikangas, Jarmo; Kutuniva, Kari; Mustakangas, Aappo (Key engineering materials, 2018)
The focus of this study was to test a low-cost level plastic printer in the multi-material printing application using principles of design for additive manufacturing (DFAM). Two sample structures were designed in the project. One of the main planning principles of the examples was to integrate multiple functions into one part and intelligently utilize a variety of materials and reduce parts count. The most common material used in the experiments was the basic PLA, which is widely used, easy-to-print and economical alternative. As special materials, electrically conductive PLA-based graphene filament and highly flexible polyurethane-based filament was used. The results show that multi-material printing is also possible with lower cost devices and it makes it easier for smart products to be manufactured cost-effectively. It has also been found that multi-material printing can be technically challenging and that further research and experiments in this subject are needed. In the future, the research topic will be even more interesting as equipment and materials will develop. This paper presents detailed printing parameters for all the materials used in the printing tests.